2022
DOI: 10.1101/2022.02.14.22270780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analyses of ADHD identify 27 risk loci, refine the genetic architecture and implicate several cognitive domains

Abstract: Attention deficit hyperactivity disorder (ADHD) is a prevalent childhood psychiatric disorder, with a major genetic component. Here we present a GWAS meta-analysis of ADHD comprising 38,691 individuals with ADHD and 186,843 controls. We identified 27 genome-wide significant loci, which is more than twice the number previously reported. Fine-mapping risk loci highlighted 76 potential risk genes enriched in genes expressed in brain, particularly the frontal cortex, and in early brain development. Overall, ADHD w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 99 publications
(151 reference statements)
4
57
0
Order By: Relevance
“…21,22,25 Our results show that such relationships are also evident in a populationbased sample of children, linking poorer cognitive functioning in each of the three phenotypes with increased ADHD traits. The association between higher ADHD PRSs and poorer working memory accuracy as well as increased reaction time variability are consistent with prior findings where ADHD-PRS was significantly associated with decreased working memory in an independent cohort, 11 and other studies linking dysfunctions of these mechanisms to ADHD genetic risk factors, 3,82,83 providing further weight to the conceptualisation of working memory and reaction time variability as endophenotypes for ADHD. Partial mediation observed for working memory confirms previous results from a case-control study, 42 but contrasts the full mediation identified for working memory linking ADHD PRSs and symptoms of hyperactivity/impulsivity, 14 suggesting that gene-cognition-trait relationships might differ between ADHD symptom domains.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…21,22,25 Our results show that such relationships are also evident in a populationbased sample of children, linking poorer cognitive functioning in each of the three phenotypes with increased ADHD traits. The association between higher ADHD PRSs and poorer working memory accuracy as well as increased reaction time variability are consistent with prior findings where ADHD-PRS was significantly associated with decreased working memory in an independent cohort, 11 and other studies linking dysfunctions of these mechanisms to ADHD genetic risk factors, 3,82,83 providing further weight to the conceptualisation of working memory and reaction time variability as endophenotypes for ADHD. Partial mediation observed for working memory confirms previous results from a case-control study, 42 but contrasts the full mediation identified for working memory linking ADHD PRSs and symptoms of hyperactivity/impulsivity, 14 suggesting that gene-cognition-trait relationships might differ between ADHD symptom domains.…”
Section: Discussionsupporting
confidence: 89%
“…Participants of European ancestry were selected for all further analyses in order to match the genetic ancestry of the discovery genome wide association study (GWAS) for ADHD used to calculate PRSs. 11, 47 To maximise the sample size for each analysis, three partially overlapping samples at 2-year follow-up were selected to ensure consistency of age across samples (details are provided in the following sections; see Figure 1 for participant demographics). Consistent with the overall prevalence of ADHD in the general population, 48 5.3% of all subjects with available parent-rated Child Behaviour Checklist (CBCL) 49 attention problems scores measured at the 2-year follow-up ( n = 5,823) would be considered to have clinical ADHD (based on 65 t-score cut-off).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each disorder GWAS [ADHD (8), schizophrenia (6), major depression (10), bipolar disorder (54), diabetes (57), heart failure (58), rheumatoid arthritis (41), and inflammatory bowl disease (59)], we constructed a score vector, , across 2155 genes that quantified the similarity of each gene to variants identified in each GWAS. The similarity was defined based on four main bioinformatic datasets including SNP position on the DNA, protein interaction network (PPI), brain eQTL, and regional gene expression across the brain as quantified using Allen Human Brain Atlas (AHBA) (47).…”
Section: Methodsmentioning
confidence: 99%
“…Following these steps, 387,392 samples with European ancestry and 557,369 variants were retained. Processing and imputation performed on the PNC genotypes has also been previously characterized, and resulted in 4,973 European ancestry samples and 4,903,082 variants retained 64 . The ABCD Data Analysis, Informatics & Resource Center (DAIRC) performed initial genotype QC according to the Ricopili pipeline recommendations, resulting in 11,099 samples and 516,598 variants retained in data release 3.0 65 .…”
Section: Polygenic Risk Scores and Validationmentioning
confidence: 99%